Processo de digestão anaeróbia em dois estágios a partir de glicerol residual e caracterização metagenômica das comunidades microbianas - Lora, Luana Bertin (My University, 2026)
Biodiesel, produced from grains, is one of the options for reducing the use of fossil fuels. The process generates crude glycerol, which contains impurities that hinder its reuse, requiring a solution for the sustainability of the process. Anaerobic digestion (AD) emerges as an alternative to convert this waste into biogas. Although traditionally carried out in a single stage, AD in two projects aimed at improving handling and energy recovery, by separating the fermentative phase - responsible for the production of H2 and volatile fatty acids (VFA) - from the methanogenic phase, in which these compounds are converted to CH4, with microorganisms playing a central role. Thus, the objective was to investigate the composition and performance of the microbial community involved in the two-stage anaerobic digestion of crude glycerol, focusing on the generation of H2 and CH4. In the fermentation stage, isolated cultures of Bacillus amyloliquefaciens (BA), Clostridium bifermentans (CB), and a co-culture formed by both were used, tested at optical densities OD (0.3 and 0.6). In 600 mL flasks containing 3% crude glycerol, evaluate H2 production, substrate consumption, VFA, and alcohol. In the methanogenic stage, the fermentation broth was used as a substrate in prolonged Biochemical Methane Potential (BMP) tests in 200 mL reactors, employing inoculum/substrate ratios (RIS) of 2:1, 3:1, and 4:1 at 37°C. Metagenomic analyses were performed at the end of the methanogenic stage using the Oxford Nanopore Promethion platform, targeting the 16S rRNA gene for bacteria and the V3V5 region of the gene for archaea. Isolated BA showed the highest H2 yield (0.34 mmol H2/mol glycerol). Anaerobic digestion in two stages improved, on average, ten times the CH4 production when using a higher RIS (2:1) compared to the single-stage process. The CB fermentation broth at a 3:1 ratio showed the highest cumulative methane production, 1280 mL. Broth RIS were more efficient in methane production. The VFAs produced by stage I were consumed by BA (87%) and BC6 (93%) in the methanogenic stage. In the BC3 broth, only acetic acid was consumed, while in the CB broth, both acetic and propionic acids were produced. Anaerobic digestion in two projects promoted changes in the methanogenic microbial community, positively associated with process performance. The acetoclastic archaea Methanotrix was more predominant in the process in two projects, as well as having a greater abundance of genes related to the acetoclastic pathway. It is concluded that two-step anaerobic digestion is an efficient strategy for utilizing residual glycerol, as it significantly increased CH4 production and favored the conversion of volatile fatty acids (VFAs), thus representing an alternative for managing this waste elimination and producing renewable energy. [resumo fornecido pelo autor]
O biodiesel, produzido a partir de grãos, é uma das escolhas para reduzir o uso de combustíveis fósseis. O processo gera o glicerol residual, que contém impurezas que dificultam seu reaproveitamento, exigindo uma solução para a sustentabilidade do processo. A digestão anaeróbia (DA) surge como alternativa para converter esse resíduo em biogás. Embora tradicionalmente realizada em estágio único, a DA em dois estágios aprimora a degradação e a recuperação energética, ao separar a fase fermentativa - responsável pela produção de H2 e ácidos graxos voláteis (AGV) - da fase metanogênica, na qual esses compostos são convertidos a CH4 com papel central dos microrganismos. Assim, o objetivo foi investigar a composição e o desempenho da comunidade microbiana envolvida na digestão anaeróbia em dois estágios do glicerol residual com foco na geração de H2 e CH4. Na etapa fermentativa, foram utilizadas culturas isoladas de Bacillus amyloliquefaciens (BA), Clostridium bifermentans (CB) e a co-cultura formada por ambas, testadas nas densidades óticas DO (0,3 e 0,6). Em frascos de 600 mL contendo 3% de glicerol residual, avaliando a produção de H2, o consumo de substrato, AGV e álcoois). Na etapa metanogênica, o caldo fermentativo foi utilizado como substrato em testes de Potencial Bioquímico de Metano (BMP) conduzidos em reatores de 200 mL, empregando as razões inóculo/substrato (RIS), 2:1, 3:1 e 4:1, a 37°C. As análises metagenômicas foram realizadas ao final da etapa metanogênica, por meio da plataforma Oxford Nanopore Promethion, direcionadas ao gene rRNA 16S para bactérias e à região V3V5 do gene para arqueias. BA isolado apresentou o maior rendimento de H2 (0,34 mmol H2/mol glicerol). A digestão anaeróbia em dois estágios aumentou, em média, dez vezes a produção de CH4, ao utilizar a maior RIS (2:1) em relação ao processo em estágio único. O caldo fermentativo de CB na razão 3:1 apresentou a maior produção cumulativa de metano, 1280 mL. As maiores RIS de caldo foram mais efetivas na produção de metano. Os AGVs produzidos pelo estágio I foram consumidos por BA (87%) e BC6 (93%) no estágio metanogênico. No caldo de BC3, houve consumo apenas de ácido acético, enquanto, no caldo de CB o ácido acético e propiônico foram produzidos. A digestão anaeróbia em dois estágios promoveu mudanças na comunidade microbiana metanogênica, associadas positivamente ao desempenho do processo. A arqueia acetoclástica Methanotrix teve maior predominância no processo em dois estágios bem como maior abundância de genes relacionados à via acetoclástica. Conclui-se que a digestão anaeróbia em dois estágios é uma estratégia eficiente para o aproveitamento do glicerol residual, pois aumentou significativamente a produção de CH4 e favoreceu a conversão dos AGVs, configurando-se como uma alternativa para o manejo desse resíduo e a produção de energia renovável. [resumo fornecido pelo autor]
Keywords: Digestão anaeróbia; Biotecnologia; Hidrogênio; Metano; Anaerobic digestion; Biotechnology; Hydrogen; Methane